2015
DOI: 10.1149/06901.0113ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Challenges with Quantum Chemistry-Based Screening of Electrochemical Stability of Lithium Battery Electrolytes

Abstract: Challenges with the quantum chemistry based-screening of electrochemical stability of solvents and salts with potential applications in lithium batteries are discussed. Initial high throughput screening of carbonate and phosphate-based electrolyte solvents provided insight into first and second reduction and oxidation potentials and reorganization energies of these solvents. It has been found that it was important to include a lithium cation in the screening of semifluorinated solvents. Two reduction pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…Additional simulations have revealed that the reduction voltage of the one-electron and two-electron reduction reactions of EC are not exactly the same. Borodin et al 79,80 screened about~100 carbonate molecules and 300 phosphate molecules and found that the second electron reduction potential is higher than the first reduction potential for the majority of them, indicating that if these singly reduced species stick near the negative electrode long enough, they are likely to undergo the second reduction reaction.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…Additional simulations have revealed that the reduction voltage of the one-electron and two-electron reduction reactions of EC are not exactly the same. Borodin et al 79,80 screened about~100 carbonate molecules and 300 phosphate molecules and found that the second electron reduction potential is higher than the first reduction potential for the majority of them, indicating that if these singly reduced species stick near the negative electrode long enough, they are likely to undergo the second reduction reaction.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…Density functional theory (DFT) computational methods are widely applied to calculate the electronic properties of ionic liquids on the case-by-case basis. Meanwhile, the so-called high-throughput approach is applied to conduct screening of components of aqueous and organic solvent electrolytes in search for the best candidates for their practical applications [3][4][5][6][7][8][9], for example, in the so-called electrolyte genome project [10]. However, this approach has not yet been fully applied for screening ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the process is repeated on a smaller number of candidates, and usually using accurate methods. The high-throughput approach was used to find the best components for energy storage systems [3][4][5][6][7][8][9][10]. Cheng et al screened 1400 organic molecules for use in non-aqueous redox-flow batteries [11]; they down-selected the candidates using DFT-based descriptors for redox potentials, solubility, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…55,89,90 Finally, other semifluorinated solvents such semifluorinated DMC, sulfolane were also predicted in QC calculations to yield LiF generation at high potentials if salt concentration is high enough to ensure Li + contact with fluorine of the solvent, which is not energetically probable at low salt concentrations. 85,91 Currently, there are not too many experimental examples of the successful demonstrations of protective in situ CEI formation on conversion type cathodes. Yet, we would like to highlight some of them to show the generality of the approach and also to share a current knowledge foundation that, we believe, is useful for the prediction of other classes of possibly suitable electrolyte compositions that may be identified in the future, either experimentally or by using QC or other suitable calculation methodologies.…”
mentioning
confidence: 99%
“…Overall, we expect that a broad range of other electrochemically unstable (within the 1.2-4 V versus Li/Li + potential window) and radical-generating (upon oxidation) metal salts may be effective in the formation of the strongly cross-linked CEI on conversion-type cathodes. For example, defluorination of semifluorinated carbonates such as FEC, FDMC or semifluorinated sulfones occurring above 1.2 V versus Li/Li + according to DFT calculations 91 also yields radicals that could also polymerize and form a protective film. Furthermore, we expect that by tuning the composition and properties of the radical-generating salt additives one may reduce the thickness and improve the properties of the protective CEI for a broad range of electrolyte solvent compositions.…”
mentioning
confidence: 99%